Comparative evaluation of gamma cameras performance for internal monitoring of workers exposed to I-131 in nuclear medicine services - Salomão Marques de Oliveira; Ana Letícia Almeida Dantas; Bernardo Maranhão Dantas (Brazilian Journal of Radiation Sciences)
Introduction: In the nuclear medicine practice, a variety of radionuclides are handled for diagnostic and therapy which represents a significant risk of internal and external exposure for workers. Such occupational exposure requires the implementation of a routine monitoring plan, including intakes of radionuclides. Currently, in Brazil, approximately 90 Nuclear Medicine Services (NMS) are authorized by the Nacional Nuclear Energy Commission of Brazil to handle 131I for therapy purposes [1], resulting in a significant number of workers routinely exposed to internal exposures. 131I remains as one of the most frequently used radionuclides in NMS, and presents higher risks of intake and internal doses. The International Atomic Energy Agency recommends implementing an internal monitoring program of this group of workers. However, in Brazil there are not qualified laboratories to attend the demand of internal monitoring [2].